2011
DOI: 10.1103/physrevb.84.214529
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the ac magnetic susceptibility of superconducting films via magneto-optical imaging

Abstract: We have established a link between the global ac response and the local flux distribution of superconducting films by combining magnetic ac susceptibility, dc magnetization, and magneto-optical measurements. The investigated samples are three Nb films: a plain specimen, used as a reference sample, and other two films patterned with square arrays of antidots. At low temperatures and small ac amplitudes of the excitation field, the Meissner screening prevents penetration of flux into the sample. Above a certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 42 publications
(51 reference statements)
10
22
0
Order By: Relevance
“…This is also true for thermomagnetic avalanches, where finger-like penetration consisting of a main trunk and small branches at 90 • , has been observed in Pb and Nb samples with square arrays of antidots [18,19]. Fig.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…This is also true for thermomagnetic avalanches, where finger-like penetration consisting of a main trunk and small branches at 90 • , has been observed in Pb and Nb samples with square arrays of antidots [18,19]. Fig.…”
Section: Resultsmentioning
confidence: 66%
“…As a matter of fact, avalanches with secondary branches at 90 • of the main bole have been reported by Vlasko-Vlasov et al [17], Menghini et al [18], and Motta et al [19]. The observations described in the first of those papers also include 45 • branching, a case which was treated theoretically by Aranson et al [20].…”
Section: Introductionmentioning
confidence: 54%
“…These flux jumps were interpreted as a thermomagnetic instability of the critical state. It was demonstrated that in a sample with an array of antidots flux jump propagates along the antidots row [10]. Nucleation of the superconducting phase in a thin surface sheath in decreasing magnetic fields parallel to the sample surface was predicted by Saint-James and de Gennes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Panel 1(c) shows dendritic structures, typical of plain films, here shown for a 2.5 Â 2.5 mm 2 sample. 26 Panels 1(d) and 1(e) exhibit straight tracks in the flux penetration, evidently guided by the rows of ADs, 7,9,10 in the specimens UNI and GRAD, respectively. Figure 2 depicts the effects on the critical current of a film of a-Mo 79 Ge 21 , caused by the insertion of different arrays of ADs.…”
mentioning
confidence: 99%
“…6 It has been demonstrated that the insertion of arrays of ADs in a superconducting film can lead, at high temperatures, to an increase of the critical current. 6 Unfortunately, at low temperatures, such PCs facilitate the proliferation of flux channeling [7][8][9][10] leading to unwanted instabilities of thermomagnetic origin 11,12 which render the superconductor impractical. A good compromise between strong pinning and lack of channeling can be achieved by introducing a quasiperiodic array of PCs, as suggested theoretically by Misko et al [13][14][15] and confirmed experimentally by Kemmler et al 16 and Silhanek et al 17 This aperiodic distribution of pinning centers may be further optimized by matching it to the typically non-uniform distribution of vortices.…”
mentioning
confidence: 99%